Adolescents’ academic performance: what helps them and what hinders them from achievement and success? - Horanicova, Simona; Husarova, Daniela; Madarasova Geckova, Andrea; Lackova Rebicova, Miriama; Sokolova, Lenka; de Winter, Andrea F.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2024)
Research on adolescents' academic performance has mostly focused on the contribution of objective factors, such as socioeconomic situation of the family or individual cognitive skills and school results. Evidence with a focus on adolescents' subjective experiences is scarce. The aim of this qualitative study was to explore factors related to adolescents' academic performance from their perspectives.We used data from 11 group semi-structured interviews conducted in 2020/2021 with 45 adolescents in the first year of high school in Slovakia (mean age= 14.98; 22.2% boys). Participants were selected from three types of high school with regards to the graduation system. We analysed the data using consensual qualitative research and thematic analysis.Results: Based on the statements of the adolescents, we identified five main themes of factors that affect their academic performance. Adolescents reported that the following contribute to their academic performance: the contents and methods of teaching; how teachers behave and do their jobs; the way in which adolescents study and what motivates them; support within and outside the school, and the environment and appearance of the school. Adolescents reported that improving the curricula and using teaching methods that balance theoretical information with practical skills training would help their academic performance immensely.We identified several factors related to adolescents' academic performance using their own perspectives and experiences. Strengthening the capacities of teachers may largely benefit adolescents' educational process and further academic performance.